The development of measurement instruments of Sharia students' perceptions about Khilafah - Subando, Joko; Wibowo, Muhammad Kurniawan Budi; Farkhani, Farkhani (Graduate School of Universitas Negeri Yogyakarta & Himpunan Evaluasi Pendidikan Indonesia (HEPI), 2023)
This study aims to develop an instrument to measure Sharia students' perception of the Khilafah. The research applied the ADDIE development research approach. The activity began with reviewing Taqiyuddin An-Nabhani's books and articles about Khilafah to get the instrument construct (analysis). The next stage was to compile the grid and assemble the instrument items (design). The items of the assembled instrument were then assessed by 11 experts (development). The validated Instruments were then carried out with limited and expanded trials. The limited trial was conducted on 26 students at Universitas Islam Negeri (UIN) Salatiga, and the expanded trial was conducted on 227 Sharia students from Institut Islam Mamba'ul